여러 레진계 치아고정 재료의 굴곡강도 및 탄성계수 비교 - 유제인(Je-In Yoo); 김수연(Soo-Yeon Kim); Bayarchimeg Batbayar; 김진우(Jin-Woo Kim); 박세희(Se-Hee Park); 조경모(Kyung-Mo Cho) (Journal of dental rehabilitation and applied science, 2016)
Purpose: Direct splinting material should have high flexural strength to withstand force during mastication and low modulus of elasticity to provide some movement while force applied for relief of stress. The purpose of this study was to compare flexural strength and modulus of elasticity of several resinous splinting materials. Materials and Methods: Four materials; Super-Bond C&B, G-FIX, G-aenial Universal Flo, FiltekTM Z350 XT; were used in this study. Fifteen rectangular bar specimens of each material were prepared. Three-point bending test were performed to determine physical properties. Maximum load at fracture was recorded and flexural strength and modulus of elasticity were calculated. One-way analysis of variance (ANOVA) and Scheffe's tests at a 0.05 level of significance were conducted on all test results. Results: Statistical analysis reveals that Super-Bond C&B had significant low mean value for flexible strength and the other three materials showed no significant difference. For modulus of elasticity, Super-Bond C&B exhibited statistically lower modulus of elasticity. G-FIX presented intermediate result, showing statistically higher modulus of elasticity than Super-Bond C&B but lower than G-aenial Universal Flo and FiltekTM Z350 XT. There was no significant difference on modulus of elasticity between G-aenial Universal Flo and FiltekTM Z350 XT. Conclusion: Using a G-FIX, the newly commercially available splinting material, which shows higher fracture resistance properties comparable to flowable and restorative composite resin and a relatively flexible nature might be a beneficial for stabilizing teeth mobility. 목적: 본 연구의 목적은 수종의 레진계 치아고정 재료의 굴곡강도와 탄성계수를 비교 분석하는 것이다. 연구 재료 및 방법: 레진계 치아고정 재료로 Super-Bond C&B (SB), G-FIX (GF), G-aenial Universal Flo (GU), Filtek Z350 XT (FZ)를 이용하여 각 군당 15개씩 총 60개의 시편을 제작하였다. 3점 굽힘 시험으로 측정된 값에 따라 굴곡강도와 탄성계수를 계산하였다. 실험값은 One-way ANOVA test로 분석하고, Scheffe's test로 사후 검정하였다. 결과: 본 연구의 결과 SB는 다른 재료들과 비교 시 가장 낮은 굴곡강도를 보였으며 GF, GU, FZ는 비슷하게 높은 굴곡강도를 보였다. 탄성계수의 경우 SB가 가장 낮은 값을 보였고 GF는 SB보다는 높지만 GU와 FZ보다는 낮은 탄성계수를 보였으며 GU와 FZ는 유의하게 높은 탄성계수를 보였다. 결론: 동요치 고정을 목적으로 새로 개발된 GU (G-FIX)는 유동성 복합 레진과 수복용 복합 레진과 같이 높은 강도를 보이며 잘 파절되지 않으면서도 상대적으로 유연한 성질을 보여 동요치 고정에 유리할 것으로 사료된다.